UPAYA MENINGKATKAN HASIL BELAJAR SUDUT BERELASI DI BERBAGAI KUADRAN DENGAN MENGGUNAKAN e-MODUL PADA SISWA KELAS X TKJ 3 SMKN 4 PEKANBARU TAHUN 2019 - Fitriani Fitriani (Universitas Negeri Medan, 2022)
Efforts to Improve Related Angle Learning Outcomes In Various Quadrants By Using E-Modules In Class X Students Of Tkj 3 Smkn 4 Pekanbaru In 2019. the problem to be studied in this action research is: can using e-modules improve learning outcomes of related angles in various quadrants in class X TKJ3 students of SMK Negeri 4 Pekanbaru city in 2019. The research objectives to be obtained are: (a) To determine the learning activities of students in mathematics by using e-modules. (b) To improve student learning outcomes in class X TKJ3 SMKN 4 Pekanbaru. This study uses two rounds of action research. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is the students of Class X TKJ3. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. Based on the results of observations and data processing that there was an increase in student learning outcomes in the second cycle where all activities increased with an average percentage of 77.38% and included in the Very Good category. In general, the average student learning activity in the first cycle was 3.8 with a Good category, while in Cycle II the average student activity became 4.1 with a Very Good category. The average student learning activities in cycles I and II are in the Good category. Based on the data above, the writer concludes that e-modules can improve learning outcomes related angles in various quadrants in mathematics subjects and have a positive impact on student learning activities, especially in class X TKJ3 students.